Importancia del conocimiento de la entomología en la formación del médico en Risaralda, Colombia - Agudelo Ospina, Jeison Andrés; Alzate-Carvajal, Catalina; Arroyave Castaño, Andrés Felipe; Manrique-Castaño, Santiago; Quiroga Mendoza, Camilo Andrés; Sarria Gómez, Daniela; Yepes Echeverri, María Camila; Rodriguez-Morales, Alfonso J. (Revista Médica de Risaralda, 2013)
N/A.